An investigation into the psychology of luxury consumption – especially why more young Chinese are keen on luxury fashion goods nowadays? - Lin, Xia (2013)
This dissertation aims at investigating the phenomenon that more young Chinese are keen on luxury fashion goods nowadays. The majority of the existing research studies on Chinese luxury consumption motivation are mainly focused on an older target group such as the “new rich” and middle class but neglect a large and growing segment of non-wealthy young luxury consumers in China. Therefore, this dissertation is going to fill this gap.